Effects of a 16-week dance intervention on loneliness and self-esteem in left behind children: a randomised controlled trial - Xiaolin Li; Qian Yang; Jiayi Long; Linghui Zhou; Chunxia Lu; Zhenqian Zhou; Ming Zeng; Weixin Dong (Scientific Reports)
Abstract Loneliness and low self-esteem are among the more prominent mental health problems among left-behind children, but most of the current research stays in cross-sectional surveys, with fewer studies proposing specific solutions. In addition, although the effective impact of dance interventions on loneliness and self-esteem has been demonstrated, the impact in the group of left-behind children remains under-explored. Therefore, this study validated the effectiveness of a dance intervention on loneliness and self-esteem in left-behind children through a 16-week randomised controlled trial. Stratified sampling was used to select one primary school from each of the 14 cities in Hunan Province, with a maximum of 100 children recruited from each primary school. Independent researchers used SPSS 29.0 to randomly assign the eligible 1270 participants to the Experimental group (n = 635) and Control group (n = 635) in a 1:1 ratio. The Experimental group performed 45 min of moderate-intensity dance training five times a week. The Control group maintained their original living conditions. Participants were measured three times using the Children’s Loneliness Scale and Rosenberg’s Self-Esteem Scale: baseline (T0), after 8 weeks (T1), and post-intervention (16 weeks, T2). Linear mixed-effects models for repeated measures were used to test the effects of time, group and time × group interactions. (a) The average age of the 1261 participants was 10 years (SD = 3.52), with high levels of loneliness (42.48 ± 12.04) and low levels of self-esteem (26.75 ± 6.39). (b) There was a significant negative correlation between loneliness and self-esteem among the LBC (p < 0.001, r = − 0.390). (c) After the dance intervention, the LBC’s loneliness significantly decreased [F (2, 1258) = 74.516, η p 2 = 0.106, p < 0.001] and their self-esteem significantly increased [F (2, 1258) = 73.64, η p 2 = 0.104, p < 0.001]. A 16-week dance intervention is an effective strategy to improve loneliness and self-esteem in LBC. Given the acceptability and practicality of the dance intervention, it could be included in a health programme to improve loneliness and self-esteem in LBC.